Function Analysis of P450 and GST Genes to Imidacloprid in Aphis craccivora (Koch) - Yang, Yuan-Xue; Lin, Rong-Hua; Li, Zhuo; Wang, Ai-Yu; Xue, Chao; Duan, Ai-Ling; Zhao, Ming; Zhang, Jian-Hua (Frontiers in Physiology, 2021)
Aphis craccivora (Koch) is an economically important pest that affects legumes in worldwide. Chemical control is still the primary efficient method for A. craccivora management. However, the mechanism underlying insecticide resistance in A. craccivora has not been elucidated. A previous study observed that piperonyl butoxide (PBO) and diethyl maleate (DEM) significantly synergized imidacloprid in A. craccivora field populations, indicating that cytochrome P450 (P450) and glutathione S-transferase (GST) genes may play pivotal roles in imidacloprid resistance. In this study, thirty-eight P450 genes and ten GST genes were identified in A. craccivora through transcriptomic analysis. The expression levels of these P450 and GST genes were measured in susceptible (SUS) strains of A. craccivora under imidacloprid treatment with LC15, LC50, and LC85 doses. The expression levels of CYP18A1, CYP6CY21, CYP6DA1, CYP6DA2, CYP4CJ1, CYP4CJ2, and CYP380C6 were up-regulated in the three treatments. Most of these genes belong to CYP3 and CYP4 Clans. In addition, the expression levels of all P450 and GST genes in A. craccivora were also measured in the Juye (JY) and Linqing (LQ) field populations. The expression levels of CYP6DA2, CYP4CJ1, and CYP380C6 were up-regulated in the SUS strain after imidacloprid treatment at three doses, and these genes were overexpressed in the JY population. Furthermore, the sensitivity of A. craccivora to imidacloprid was significantly increased after knockdown of CYP380C6 and CYP6DA2 through RNA interference. These results may help to elucidate the mechanisms underlying of imidacloprid resistance in A. craccivora.